Platelet factor 4 regulates T cell effector functions in malignant pleural effusions. (28th October 2020) - Mulet, Maria; Zamora, Carlos; Porcel, José M.; Nieto, Juan C.; Pajares, Virginia; Muñoz-Fernandez, Ana M.; Calvo, Nuria; Esquerda, Aureli; Vidal, Silvia
Abstract: Malignant pleural effusion (MPE) is defined as the presence of tumor cells in pleural fluid and it is a fatal complication of advanced lung adenocarcinoma (LAC). To understand the immune response to the tumor in MPE, we compared the concentration of immunomodulatory factors in MPE of LAC and pleural effusion of heart failure (HF) patients by ELISA, and the proliferation and cytotoxic phenotype of T cells stimulated in the presence of LAC and HF pleural fluids by cytometry. Platelet factor 4 (PF4), vascular endothelial growth factor (VEGF), transforming growth factor beta (TGF-β) and P-selectin levels were higher in LAC than in HF pleural fluids. However, plasmatic PF4 and P-selectin levels were similar in LAC and HF. VEGF positively correlated with TGF-β and sPD-L1 in LAC but not in HF pleural fluids. LAC pleural fluids also inhibited T lymphocyte proliferation and cytotoxicity and reduced IL-17 production. PF4 levels inversely correlated with T cell function. The high content of PF4 in MPE was associated with poor prognosis. Our findings suggest that an impaired response of T lymphocytes induced by PF4 provides a significant advantage for tumor progression. Highlights: Platelet-derived factors are present in pleural effusions. Higher levels of platelet factor 4 have been found in malignant pleural effusions from lung adenocarcinoma patients. Platelet factor 4 is implicated in the modulation of T cell effector functions in malignant pleural effusions. Platelet factor 4 has a prognostic role in lung cancer patients with malignant pleural effusions.